2018
DOI: 10.1149/2.0941803jes
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Charge-Redistribution in Double Layer Capacitors

Abstract: Charge-redistribution (CR) in electrochemical double layer capacitors (EDLCs) manifests as voltage drop during open-circuit relaxation (OCR) after galvanostatic (GS) charging, and voltage recovery during OCR after GS discharging. The complex porous structure of electrodes causes a capacitor to charge/discharge non-uniformly which causes charge-redistribution in OCR. In this work, we have used a macro-homogeneous transport model which incorporates electrolyte concentration dependent conductivity and constant ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 60 publications
0
35
1
Order By: Relevance
“…found that the temperature rise in EDLCs for Δ ψ s =2 V under galvanostatic cycling predicted by considering only Joule heating was smaller than that measured experimentally . The analysis suggested that the irreversible heat generation rate in EDLCs was the summation of (i) Joule heating and (ii) heat generation owing to charge redistribution effects modeled as dissipation through the pore resistance . In fact, the charges redistribute themselves during cycling because of the non‐uniform charging/discharging processes in the complex porous electrode structure .…”
Section: Introductioncontrasting
confidence: 54%
See 2 more Smart Citations
“…found that the temperature rise in EDLCs for Δ ψ s =2 V under galvanostatic cycling predicted by considering only Joule heating was smaller than that measured experimentally . The analysis suggested that the irreversible heat generation rate in EDLCs was the summation of (i) Joule heating and (ii) heat generation owing to charge redistribution effects modeled as dissipation through the pore resistance . In fact, the charges redistribute themselves during cycling because of the non‐uniform charging/discharging processes in the complex porous electrode structure .…”
Section: Introductioncontrasting
confidence: 54%
“…This could be attributed to the heat generation associated with charge redistribution effects in the porous carbon electrode and modeled as the leakage current dissipated through the pore resistance . Indeed, the pore resistance is responsible for self‐discharge (leakage current) in EDLCs along with other parasitic reactions, such as electrolyte decomposition, and oxidation/reduction of carbon surface functional groups . In addition, this contribution increased with increasing potential window as the pore resistance also increased with increasing potential window .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past three decades, numerous studies have been conducted that exploit some form of the RC transmission line model to understand the selfdischarge mechanism [8][9][10], the effect of pore size and shape [11][12][13][14][15][16][17][18], and the effect of electrolyte concentration [19,20], among others [21]. More recently, several studies have argued for more detailed analysis of ion transport inside the DL [4,5,[22][23][24][25][26].…”
mentioning
confidence: 99%
“…[27] Kroupa et al [28] extended the model of Verbugge and Liu by an additional dimension to account for the transport into the carbon particles. Madabattula and Kumar [29] gave insights in the charge redistribution that occurs during high current charging and discharging.…”
Section: Introductionmentioning
confidence: 99%